INDUCTION OF LABOUR WITH SUBLINGUAL MISOPROSTOL COMPARED TO VAGINAL DINOPROSTONE IN TERMS OF NEONATAL OUTCOME IN WOMEN WITH PROLONGED PREGNANCY - BANO, S; YOUSAF, S; SAJJAL, W; JAVAD, S; ALTAF, B (Biological and Clinical Sciences Research Journal, 2024)
Labor induction in postdate pregnancies can impact neonatal outcomes, including Apgar scores and the need for NICU care. Various induction agents, such as sublingual misoprostol and vaginal dinoprostone, offer differing efficacies. This study aims to compare the neonatal outcomes of these two agents to determine the more effective option for labor induction in postdate pregnancies. Objective: To compare neonatal outcomes, specifically Apgar scores <7 at 1 minute and NICU admissions within the first 24 hours, between neonates born to postdate women induced with sublingual misoprostol versus vaginal dinoprostone. Methods: This randomized controlled trial was conducted in the Department of Obstetrics and Gynecology, Unit 1, Holy Family Hospital, Rawalpindi, from January 2024 to July 2024. After Institutional Research Forum approval, 200 women meeting the selection criteria were randomized via the lottery method into two groups. Group I received 25 mcg of sublingual misoprostol every 4 hours up to 4 doses, and Group II received 3 mg vaginal dinoprostone every 6 hours up to 2 doses. Neonatal Apgar scores were recorded at delivery, and NICU admissions were monitored within 24 hours. Data were documented on structured proforma and analyzed using SPSS. Results: The mean maternal age in Group I was 27.17±4.71 years and in Group II 28.33±4.25 years. Both groups had comparable gestational ages (41.60±0.49 vs. 41.68±0.46 weeks) and parity (1.64±0.79 vs. 2.05±0.83). Group I neonates had higher mean Apgar scores at 1 minute (7.25±2.08) compared to Group II (6.62±2.07), with significant group differences (p=0.04). NICU admissions were required in 30% of neonates, with 48.8% needing NICU care, and fewer admissions in Group I (p=0.04). NICU care showed a significant association with maternal age over 28 years (p=0.000) and nulliparous status (p=0.007) but was not significantly different for those under 28 years or multiparous. Conclusion: Sublingual misoprostol demonstrated superior efficacy to vaginal dinoprostone in labor induction for prolonged pregnancies, with improved neonatal outcomes, including higher Apgar scores and fewer NICU admissions. Age and parity influenced outcomes, highlighting sublingual misoprostol as an effective choice for better neonatal health.